(-2 1/8+2/3):0,5 (1/3-6/7)*420 2 4/7*(-4 2/3):4/5 (-7 1/5+1 2/3):(-4/15) (-1 2/3+1 1/2)*(-6)
(-2 1/8+2/3):0,5
(1/3-6/7)*420
2 4/7*(-4 2/3):4/5
(-7 1/5+1 2/3):(-4/15)
(-1 2/3+1 1/2)*(-6)
Ответ(ы) на вопрос:
(-2 1\8+2\3):0.5=(-2+(-3\24+16\24):1\2=-1 11\24*2\1=-35\24*2=-35\12= -2 11\24
(1\3-6\7)*420=(7\21-18\21)*420=11\21*420=220
2 4\7*(-4 2\3):4\5=18\7*(-14\3):4\5=-12*5\4=-15
(-7 1\5+1 2\3):(-4\15)=-5 6\15*(-15\4)=-81\15*(-15\4)=81\4=20 1\4
(-1 2\3+1 1\2)*(-6)=(-1\6)*(-6)=1
Не нашли ответ?
Похожие вопросы